Constructing a Global Learning Partnership in Physiotherapy: An Ireland–Uganda Initiative - O’Sullivan, Cliona; Kazibwe, Herman; Whitehouse, Zillah; Blake, Catherine (Frontiers in Public Health, 2017)
Background and aim: There is a strong correlation between disability and poverty and it is acknowledged that until disability issues are addressed the goal of poverty reduction in low income countries is unlikely to be achieved. Despite the high prevalence of disability in developing countries, there remains a significant shortage of rehabilitation professionals as highlighted by the WHO report, Human resources for Health (2006). The purpose of this project was to develop a collaborative and sustainable partnership to strengthen educational and research capacity in global health, disability and rehabilitation between two physiotherapy schools; University College Dublin, Ireland and Mbarara University of Science and Technology, (MUST) Uganda. This paper aims to describe the approach used and initial project outcomes. Methods: This project involved a bilateral visit to both institutions by two members of staff of respective physiotherapy programmes. These visits entailed stakeholder meetings, clinical site visits, and workshops to identify the priorities for the partnership and shape the collaboration going forward. Appreciative inquiry methodology was employed during the workshops and the 4 dimensional framework for curriculum development was used guide analysis and underpin findings. Findings: The key priorities identified were: (i) development of joint global health learning initiative, (ii) to explore the possibility of post-graduate learning and research opportunities for Ugandan colleagues and (iii) to develop joint clinical placement. The rationale and context and a plan of action is described. Discussion and conclusions: The project is ambitious and in order to be sustainable, the importance of long term inter-institutional commitment and further funding cannot be ignored. This work provides a framework for other universities and institutions wishing to undertake similar activities. Such partnerships provide rich learning opportunities for students and health professionals, and facilitate a deeper understanding of global health issues, social and cultural health determinants and development of enhanced professional skills.